1988
DOI: 10.1128/mcb.8.1.259
|View full text |Cite
|
Sign up to set email alerts
|

Primary structure of the human fgr proto-oncogene product p55c-fgr.

Abstract: Normal human c-fgr cDNA clones were constructed by using normal peripheral blood mononuclear cell mRNA as a template. Nucleotide sequence analysis of two such clones revealed a 1,587-base-pair-long open reading frame which predicted the primary amino acid sequence of the c-fgr translational product. Homology of this protein with the v-fgr translational product stretched from codons 128 to 516, where 32 differences among 388 codons were observed. Sequence similarity with human c-src, c-yes, and fyn translationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
50
1

Year Published

1988
1988
1996
1996

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 32 publications
2
50
1
Order By: Relevance
“…On the basis of the numbers of cDNA clones of each type isolated, the downstream polyadenylation site appears to be used most frequently, Alternative polyadenylation does not account for the size difference between the 2.9kb and 3.5kb c-fgr transcripts but probably contributes to heterogeneity in the lower molecular weight band on Northern blots. This result agrees with recent data from Katamine et al (1988), which suggests that the 3.5 kb transcript is an incompletely processed precursor, containing intron 2 of the c-fgr gene. Several genes have been characterised which contain alternative polyadenylation sites.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…On the basis of the numbers of cDNA clones of each type isolated, the downstream polyadenylation site appears to be used most frequently, Alternative polyadenylation does not account for the size difference between the 2.9kb and 3.5kb c-fgr transcripts but probably contributes to heterogeneity in the lower molecular weight band on Northern blots. This result agrees with recent data from Katamine et al (1988), which suggests that the 3.5 kb transcript is an incompletely processed precursor, containing intron 2 of the c-fgr gene. Several genes have been characterised which contain alternative polyadenylation sites.…”
Section: Discussionsupporting
confidence: 83%
“…In addition, the fyn protein has homology to the sequfence Ile-Pro-Asn-Tyr-SerAsn-Phe found at positions [50][51][52][53][54][55][56][57] (Figures 2 and 3), is identical to that reported by Inoue et al (1987), starting 3 bp downstream of their sequence. However, both our sequence and that of Inoue et al (1987) differ in the 5' untranslated region from that reported by Katamine et al (1988). This latter sequence was derived from a cDNA clone representing an incompletely processed c-fgr transcript containing intron 2.…”
Section: Discussioncontrasting
confidence: 40%
See 2 more Smart Citations
“…The two numbers on the right are taken from these pairwise comparisons and, again, refer to the number of identical (asterisks) and total conserved (asterisks and vertical lines) residues. The sequences are taken from the following references: c-src, Takeya and Hanafusa, 1982;fyn, Kawakami et al, 1986 andSemba et al, 1986;v-src, Takeya andHanafusa, 1982 andTaylor andHanafusa, 1983; fgr, Katamine et al, 1988;lyn, Yamanashi et al, 1987;c-yes, Sukegawa et al, 1987;hck, Quintreli et al, 1987;Isk, Marth et al, 1985;tkl, Strebhardt et al, 1985;v-crk, Mayer et al, 1988;PLC, Stahl et al, 1988. …”
mentioning
confidence: 99%